MANAJEMEN PENDIDIKAN ISLAM DALAM TINJAUAN EPISTEMOLOGI - Muhammad Arif Syihabuddin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
Abstract: This article discusses the epistemology of management of Islamic education. This study needs to be done because there are still many questions about the management of Islamic education from several experts. The discussion in this article covers the nature and understanding of the epistemology of science, the method of acquiring knowledge, and the epistemology of management knowledge of Islamic education. The results of the study in this article explain that the Epistemology of management science develops to empirical reality and rational considerations that give birth to a number of management sciences in their various loci and values. The birth of management science in the various loci of value that is pursued, is also influenced by the realities that affect the order developed by management science. The use of management research methods is in principle the same as the use of research methods in the social sciences. And One of the bases used to form a management framework for Islamic education is the absence of dualism in the delegation of tasks.Keyword: Epistemology, Islamic Education Management